Post-Anthropocentric Subject Imaginaries in Sarah Hall's "Mrs Fox", Ali Smith's "The Beholder", and Daisy Johnson's "Starver" - Yazgünoğlu, Kerim Can (English studies, 2025)
Theoretically grounded in critical posthumanities, this article explores how Sarah Hall's "Mrs Fox", Ali Smith's "The Beholder", and Daisy Johnson's "Starver" deploy the trope of metamorphosis as a narrative strategy to decentre the human subject and to resolve the conflict between self and other, human, animal, and plant. These short stories question whether the human subject, not separated from the nonhuman other, is a trans-subjective entity that is inextricably embedded within the earth or the loss of self because of morphing into other is a post-anthropocentric challenge to the Cartesian exclusion. In delving into different metamorphic entanglements, the stories advocate a sense of post-anthropocentric subjectivity that is predicated on not solely zoe-centric egalitarianism but also relational interconnectedness of humans and nonhumans. The article shows how the stories articulate metamorphosis as a way of recognition of nonhuman radical otherness, while it exemplifies the posthuman formulations through cases from each story. The contemporary British short fictions by women provide a corrective against the anthropocentric, speciesist, and sexist formulations of humans and nonhumans by formulating a zoe-centric mode of storytelling. The article concludes by presenting how the short stories emphasise the need for relating to human, animal, and vegetal bodies affectively.